Cargo of lies : the true story of a Nazi double agent in Canada - Beeby, Dean (Univ. of Toronto Press, 1996)
"On a chill autumn night in 1942, a German spy was rowed ashore from a U-boat off the Gaspe coast to begin a deadly espionage mission against the Allies. Thanks to an alert hotel-keeper's son, Abwehr agent 'Bobbi' was captured and forced by the RCMP to become Canada's first double agent." "For nearly fifty years the full story of the spy case, code-named Watchdog, was suppressed. Now, author Dean Beeby has uncovered nearly five thousand pages of formerly classified government documents, obtained through the Access to Information Act from the RCMP, the Canadian Security Intelligence Service, the Department of Justice, the National Archives of Canada, and Naval Intelligence. He has supplemented this treasure trove with research among still heavily censored FBI files, and interviews with surviving participants in the Watchdog story. Although British records of the case remain closed, Beeby also interviewed the MI5 case officer for Watchdog, the late Cyril Mills." "The operation was Canada's first major foray into international espionage, predating the Gouzenko defection by three years. Watchdog, as Beeby reveals, was not the Allied success the RCMP has long claimed. Agent 'Bobbi' gradually ensnared his captors with a finely spun web of lies, transforming himself into a triple agent who fed useful information back to Hamburg." "Beeby argues that Canadian authorities were woefully unprepared for the subtleties of wartime counter-espionage, and that their mishandling of the case had long-term consequences that affected relations with their intelligence partners throughout the Cold War."--BOOK JACKET.